Global Financial Crisis and Bulgarian Economy: from the Theory to Practice (UNWE Yearbook, 2014)
The study is divided in three parts. In the short introduction the basic ideas of the paper are summarized. The second part presents a mathematical model of a monetary economy with integrated real and financial sectors. The third chapter studies the problems of equilibrium convergence of the system with the velocity of money as the main variable driving the convergence. The forth part discusses the interplay between the real and the financial sectors under equilibrium convergence with three types of convergence- monetarist, neoclassical and neo-Keynesian. The author draws the conclusion that the destabilization of the economy is usually prompted by the financial sector.The fifths and the sixth parts of the paper are dedicated to the spread of the global financial crisis including the reaction of the economic policy in the leading industrial countries as well as the evolution of the anti-crisis economic policy in Bulgaria.